1990
DOI: 10.1002/bjs.1800771104
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ischaemia in experimental acute pancreatitis: Mechanism, significance and therapy

Abstract: Much clinical and experimental evidence suggests that pancreatic ischaemia in the early phase of acute pancreatitis is important in the development of pancreatic necrosis. While depletion of intravascular volume has often been assumed to be the main circulatory defect, an additional disturbance of pancreatic microcirculation has been demonstrated experimentally. Possible contributory mechanisms include chemical-induced vasoconstriction, direct injury of vessel wall, intravascular coagulation and increased endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
125
0
12

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(138 citation statements)
references
References 64 publications
1
125
0
12
Order By: Relevance
“…Auto digestion ofthe pancreas by activated digestive enzymes, ischemia ofthepancreas, apoptosis and ischemia-related reactive oxygen species (ROS)-associated lipid peroxidation cause pancreatic damage during acute pancreatitis (2-4, 24, 25). Microcirculation disturbance is an important pathogenetic factor during acute pancreatitis (3)(4)(5). The microcirculation of the pancreas can be measured by diffuse reflectance spectroscopy, intravital microscopy, multiple indicator dilution technique, and orthogonal polarization imaging (3,4,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auto digestion ofthe pancreas by activated digestive enzymes, ischemia ofthepancreas, apoptosis and ischemia-related reactive oxygen species (ROS)-associated lipid peroxidation cause pancreatic damage during acute pancreatitis (2-4, 24, 25). Microcirculation disturbance is an important pathogenetic factor during acute pancreatitis (3)(4)(5). The microcirculation of the pancreas can be measured by diffuse reflectance spectroscopy, intravital microscopy, multiple indicator dilution technique, and orthogonal polarization imaging (3,4,29).…”
Section: Discussionmentioning
confidence: 99%
“…Microcirculation disturbance is an important pathogenetic factor during acute pancreatitis (3)(4)(5). The microcirculation of the pancreas can be measured by diffuse reflectance spectroscopy, intravital microscopy, multiple indicator dilution technique, and orthogonal polarization imaging (3,4,29). We measured pancreatic microcirculation by orthogonal polarization imaging in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] In addition, microvascular perfusion failure is a characteristic hallmark of pancreatitis. [10][11][12] Since Panum [13] presented the first report, other researchers have reported that the pancreas is highly sensitive to ischemia. [14][15][16][17][18] In humans, acute pancreatitis may develop after embolic closure of the vessels supplying the pancreas, [19] after hypoperfusion of the pancreas during cardiac surgery [20,21] and surgery for thoraco-abdominal aneurysms, [22] after splanchnic hypoperfusion, [23] or after pancreatic transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…1. A cross-section from the abdominal computed tomography scan of the patient after developing pancreatitis endothelial permeability (Klar et al, 1990). MitogenActivated Protein Kinase (MAPK) is a downstream effector of Ras/Raf/MEK/ERK pathway and found to be activated in acute pancreatitis (Murr et al, 2003).…”
Section: Discussionmentioning
confidence: 99%